Low bone mineral content is common but osteoporotic fractures are rare in elderly rural Gambian women. - Aspray, T; Prentice, A; Cole, T; Sawo, Y; Reeve, J; Francis, R (1996)
Osteoporosis is reported to be rare in Black Africa. The low fracture incidence among North American black women is explained by a high peak bone mass and preservation of bone mineral into old age. To assess whether this is the case among Black African women, we measured bone mineral content (BMC) and bone mineral density (BMD), using single- and dual-photon absorptiometry, in 195 rural Gambian women aged over 44 years and 391 white women of comparable age from three centers in the U.K. Measurements were made at the midshaft of the radius, distal radius, lumbar spine, and femoral neck. The influence of height, weight, and nationality on BMC and BMD was analyzed. BMC and BMD decreased with age at all sites. Age, decreasing weight, but not height were independently associated with lower BMC at all sites. BMC in Gambian women was lower than in British women by 31% at the lumbar spine and 16% at the midshaft of the radius. After adjustment for age, height, and weight, BMC among Gambian women remained 24% lower at the lumbar spine and 10% lower at the radius. In women aged over 64 years, BMC at the lumbar spine was 42% lower and BMD was 31% lower in The Gambia (for all comparisons, p < 0.005). We conclude that bone mineral mass is not preserved in elderly Gambian women. However, minimal trauma fractures are rare in this population. These results challenge the concept of BMC as a primary determinant of fracture risk.